In vitro Generation of Cytotoxic T Cells With Potential for Adoptive Tumor Immunotherapy of Multiple Myeloma - Khalaf, Wafaa S.; Garg, Mamta; Mohamed, Yehia S.; Stover, Cordula M.; Browning, Michael J. (Frontiers in Immunology, 2019)
Multiple myeloma is a life-threatening haematological malignancy, which is rarely curable by conventional therapies. Immunotherapy, using tumour antigen-specific, cytotoxic T-lymphocytes, may represent an alternative or additional treatment for multiple myeloma. In this study, we used hybrid cell lines, generated by fusion of an EBV B-lymphoblastoid cell line (B-LCL) and myeloma cells, to stimulate in vitro peripheral blood lymphocytes from patients with multiple myeloma. We investigated induction of antigen-specific, cytotoxic T-lymphocytes to the well-defined tumour associated antigens hTERT, MUC1, MAGE-C1 and CS1, which have been shown to be expressed in a high proportion of cases of multiple myeloma. HLA-A2-peptide pentamer staining, interferon- and perforin ELISpot assays, as well as cytotoxicity assays were used. Following several rounds of in vitro stimulation, the hybrid cell lines induced antigen-specific, cytotoxic T-lymphocytes to four candidate tumour associated antigens in peripheral blood lymphocytes from HLA-A2+ multiple myeloma patients, using known HLA-A2 restricted peptide epitopes of the tumour associated antigens. In contrast, the HLA-A2+ myeloma cell line U266 failed to induce antigen-specific, cytotoxic T-lymphocytes in vitro. Our data indicate that B-LCL / myeloma hybrid cell lines induce antigen-specific, cytotoxic T-lymphocytes in peripheral blood lymphocytes isolated from multiple myeloma patients in vitro and may represent a novel strategy for use in adoptive immunotherapy of multiple myeloma.